Human rights and societies in transition : causes, consequences, responses - Horowitz, Shale Asher; Schnabel, Albrecht (United Nations University Press, 2004)
Exploring the contemporary international human rights regime, this volume assesses the factors predominantly responsible for human rights violations in transitions societies, long-term consequences of such violations and political remedies.